Mechanistic insight into propane dehydrogenation into propylene over chromium (III) oxide by cluster approach and Density Functional Theory calculations - Oyegoke, Toyese; Dabai, Fadimatu Nyako; Uzairu, Adamu; Jibril, Baba El-Yakubu (European Journal of Chemistry, 2020)
A preliminary study to provides insight into the kinetic and thermodynamic assessment of the reaction mechanism involved in the non-oxidative dehydrogenation (NOD) of propane to propylene over Cr2O3, using a density functional theory (DFT) approach, has been undertaken. The result obtained from the study presents the number of steps involved in the reaction and their thermodynamic conditions across different routes. The rate-determining step (RDS) and a feasible reaction pathway to promote propylene production were also identified. The results obtained from the study of the 6-steps reaction mechanism for dehydrogenation of propane into propylene identified the first hydrogen abstraction and hydrogen desorption to be endothermic. In contrast, other steps that include propane’s adsorption, hydrogen diffusion, and the second stage of hydrogen abstraction were identified as exothermic. The study of different reaction routes presented in the energy profiles confirms the Cr-O (S1, that is, the reaction pathway that activates the propane across the Cr-O site at the alpha or the terminal carbon of the propane) pathway to be the thermodynamically feasible pathway for the production of propylene. The first hydrogen abstraction step was identified as the potential rate-determining step for defining the rate of the propane dehydrogenation process. This study also unveils that the significant participation of Cr sites in the propane dehydrogenation process and how the Cr high surface concentration would hinder the desorption of propylene and thereby promote the production of undesired products due to the stronger affinity that exists between the propylene and Cr-Cr site, which makes it more stable on the surface. These findings thereby result in Cr-site substitution suggestion to prevent deep dehydrogenation in propane conversion to propylene. This insight would aid in improving the catalyst performance.